Endothelial Microparticles Act as Novel Diagnostic and Therapeutic Biomarkers of Diabetes and Its Complications: A Literature Review. (10th October 2016) - Deng, Fan; Wang, Shuang; Zhang, Liangqing
Abstract : Diabetes mellitus- (DM-) related vascular diseases attract increased attention due to their high morbidity and mortality. The incidence of obesity, atherosclerosis, coronary heart disease, hypertension, and dyslipidemia is significantly higher in DM patients, with an earlier onset and faster progression compared with non-DM patients. DM-related vascular diseases including macrovascular and microvascular complications are characterized by endothelial dysfunction. Therefore, a better understanding of the etiology and mechanisms of endothelial dysfunction is important for the diagnosis and treatment of DM. Endothelial microparticles (EMPs) are new diagnostic and therapeutic targets and biomarkers in DM-related vascular disease. Circulating EMPs containing biologically active substances act as intercellular signals under physiological and pathological conditions. They serve as biological markers of altered vascular endothelium and reflect the pathological progression and diminished endothelial function of blood vessels. Recent evidence suggests that the plasma level of EMPs is significantly higher in DM patients than in healthy population and is significantly correlated with DM-related complications. These observations have prompted speculation that EMPs play a crucial role in the pathophysiology of DM. This review summarizes the known and potential roles of EMPs in the diagnosis, staging, treatment, and clinical prognosis of DM and related vascular diseases.